IMPLEMENTASI PEMASARAN DIGITAL SYARIAH PADA USAHA MENENGAH: (Studi Kasus Warung Makan Pecak Belut Bu Niti Desa Tegalmlati Kecamatan Petarukan Kabupaten Pemalang) - Qurrota A’yun; Via Syifaul Awwaliyah (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
Digital marketing is a marketing activity that uses various media for a business. Digital Marketing in its application will not be unfamiliar with the name marketing mix or what is usually called marketing mix. Marketing mix is ​​a set of tools used to achieve marketing objectives. In general, the marketing mix focuses on strategic interpretation that combines product, price, promotion and place. There are additional 3Ps that complement marketing strategy, namely people, process, and physical evidence which form the 7Ps of the marketing mix. These seven Ps must be combined to suit plant growth conditions. The actual combination used will depend on the marketing team's expertise taking into account raw materials, managers and experience. The aim of this research is to explain how digital marketing is implemented through 7p marketing at Warung Makan Pecak Belut Bu Niti Kecamatan Petarukan Kabupaten Pemalang. This research is a type of qualitative research with field research to obtain primary data from interviews with informants. In this case, the subject of this research is the owner of the Pecak Belut, namely Mrs. Casniti, Lestari as an assistant and at the same time who manages the marketing and promotion of the Pecak Belut and Mrs. Sri as the head of the kitchen and then added as a buyer resource at Bu Niti's Pecak Belut Food Stall. Data analysis method used in This research includes data reduction, data presentation, and drawing conclusions.  The results of this research show that Warung Makan Pecak Belut Bu Niti implements the 7p digital marketing mix, all of which is in accordance with Islamic business ethics. Apart from that, Warung Makan Pecak Belut Bu Niti also applies sharia marketing characteristics, namely divine, akhlaqiyyah, realistic and humanistic.